2021
DOI: 10.57040/jet.v1i1.92
|View full text |Cite
|
Sign up to set email alerts
|

The eNaira - Opportunities and challenges

Abstract: Emerging technology activities are evolving and turning our world into a digital world. The digital world offers many digital inventions such as digital currency, smart devices, social media, digital devices, and the list continues. Digital or electronic currency initiatives such as eNaira are fast becoming a norm across countries as means of payment for goods and services. But many are concerned and worried about eNaira, lack of understanding of the opportunities and challenges of eNaira, and limited academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Fabian, et al (2022) in their research on E-Naira Digital Currency and the Financial Performance of Listed Deposit Money Banks in Nigeria concluded that the adoption of Central Bank Digital Currency (CBDC) has a significant relationship with the financial performance of listed deposit money banks in Nigeria. Chukwuere (2021), in his paper, titled the eNaira -Opportunities and Challenges found that the eNaira presents some opportunities for the central bank of Nigeria (CBN) and customers (Nigerians). It assists customers to access their money quickly, and CBN can monitor and control transactions and many more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fabian, et al (2022) in their research on E-Naira Digital Currency and the Financial Performance of Listed Deposit Money Banks in Nigeria concluded that the adoption of Central Bank Digital Currency (CBDC) has a significant relationship with the financial performance of listed deposit money banks in Nigeria. Chukwuere (2021), in his paper, titled the eNaira -Opportunities and Challenges found that the eNaira presents some opportunities for the central bank of Nigeria (CBN) and customers (Nigerians). It assists customers to access their money quickly, and CBN can monitor and control transactions and many more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author argues that eNaira can increase financial inclusion and mitigate AML/CFT risks, but the use of eNaira may be affected by the poor culture of compliance, employee fraud and money laundering (Esoimeme, 2021). Chukwuere (2021) shows that eNaira can assist Nigerians to access their money quickly, and the central bank can monitor and control transactions. However, the major challenge of eNaira is the issue of trust in eNaira (Chukwuere, 2021).…”
Section: Studies On Enairamentioning
confidence: 99%
“…Chukwuere (2021) shows that eNaira can assist Nigerians to access their money quickly, and the central bank can monitor and control transactions. However, the major challenge of eNaira is the issue of trust in eNaira (Chukwuere, 2021). Fabian et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, widespread availability, internet connectivity, portability and ease of use of mobile-based interventions are both acceptable and feasible to be used for patients diagnosed with schizophrenia. Mobile-based technologies are nowadays accessible to socially and economically disadvantaged people [64,65]. This paves the way for better health equity and inclusivity [66].…”
Section: Advantagesmentioning
confidence: 99%